ELECTRICAL CONDUCTIVITY OF POTASSIUM SALT–DIMETHYLSULFOXIDE–WATER SYSTEMS AT DIFFERENT TEMPERATURES (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Interactions of potassium salt–dimethylsulfoxide (DMSO)–water systems in 25–45°C temperature range were studied using electrical conductivity method. The results show that the conductance of these solutions depends on anions salvation state and is reduced according to this row: NO$^–_–3$>Cl–>I–>Br–. Ion mobility increases with rising of temperature, which leads to an increase in the limiting conductance. With the addition of DMSO appears an extreme point on the dependence, which becomes more harshly when the temperature increases. At DMSO high concentrations (>1.60 M), K+–DMSO interaction becomes more intensive, which leads to the formation of bulky solvate shell affecting negatively on the ion mobility.
Keywords: potassium salts; electrical conductivity; dimethylsulfoxide; interaction